Genomic Information may Inhibit Weight-Related Behavior Change Inclinations among Individuals in a Fear State - Persky, Susan (Ann Behav Med, 2016)
BACKGROUND: As evidence mounts regarding associations between genetics and body weight, it is essential to understand how to communicate this information, and factors like emotion that could moderate the effectiveness of messages. PURPOSE: We assessed influences of emotion on reactions to weight-related genomic information in a virtual clinical setting. METHODS: An online representative US sample of overweight women was randomized to receive an emotion induction (anger, fear, or neutral) paired with information about genomic or behavioral influences on weight in an interaction with a virtual doctor. RESULTS: Receiving genomic information led to reduced attributions of lifestyle causes for weight and behavioral intentions, but only among individuals in a fear state. CONCLUSIONS: The current study is among the first to reinforce the concern that discussing genomic underpinnings of overweight could undercut health behavior, and highlights the importance of identifying factors like emotion that influence interpretation of genomic information.